Effect of n-3 long chain polyunsaturated fatty acid supplementation in pregnancy on infants' allergies in first year of life: randomised controlled trial. (30th January 2012) - Palmer, D J; Sullivan, T; Gold, M S; Prescott, S L; Heddle, R; Gibson, R A; Makrides, M
Abstract : Objective To determine whether dietary n-3 long chain polyunsaturated fatty acid (LCPUFA) supplementation of pregnant women with a fetus at high risk of allergic disease reduces immunoglobulin E associated eczema or food allergy at 1 year of age. Design Follow-up of infants at high hereditary risk of allergic disease in the Docosahexaenoic Acid to Optimise Mother Infant Outcome (DOMInO) randomised controlled trial. Setting Adelaide, South Australia. Participants 706 infants at high hereditary risk of developing allergic disease whose mothers were participating in the DOMInO trial. Interventions The intervention group (n=368) was randomly allocated to receive fish oil capsules (providing 900 mg of n-3 LCPUFA daily) from 21 weeks' gestation until birth; the control group (n=338) received matched vegetable oil capsules without n-3 LCPUFA. Main outcome measure Immunoglobulin E associated allergic disease (eczema or food allergy with sensitisation) at 1 year of age. Results No differences were seen in the overall percentage of infants with immunoglobulin E associated allergic disease between the n-3 LCPUFA and control groups (32/368 (9%) v 43/338 (13%); unadjusted relative risk 0.68, 95% confidence interval 0.43 to 1.05, P=0.08; adjusted relative risk 0.70, 0.45 to 1.09, P=0.12), although the percentage of infants diagnosed as having atopic eczema (that is, eczema with associated sensitisation) was lower in the n-3 LCPUFA group (26/368 (7%) v 39/338 (12%); unadjusted relative risk 0.61, 0.38 to 0.98, P=0.04; adjusted relative risk 0.64, 0.40 to 1.02, P=0.06). Fewer infants were sensitised to egg in the n-3 LCPUFA group (34/368 (9%) v 52/338 (15%); unadjusted relative risk 0.61, 0.40 to 0.91, P=0.02; adjusted relative risk 0.62, 0.41 to 0.93, P=0.02), but no difference between groups in immunoglobulin E associated food allergy was seen. Conclusion n-3 LCPUFA supplementation in pregnancy did not reduce the overall incidence of immunoglobulin E associated allergies in the first year of life, although atopic eczema and egg sensitisation were lower. Longer term follow-up is needed to determine if supplementation has an effect on respiratory allergic diseases and aeroallergen sensitisation in childhood. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12610000735055 (DOMInO trial: ACTRN12605000569606).